The neuroethology of escape in crabs: From sensory ecology to neurons and back - Hemmi, Jan M. (2011)
A major challenge in neurobiology is to understand how brains function in animals behaving in the complexity of their natural environment. Progress will depend on our ability to correctly interpret results from laboratory experiments in the light of information processing demands identified by studying the organization of behaviour and the flow of information in naturally behaving animals. Predator avoidance responses of semi-terrestrial crabs offer an excellent opportunity for such an approach. We review here findings from two distinct lines of research: (1) Field studies which have characterized the structure and context of escape behaviour to real and dummy predators, and (2) Laboratory studies which have used computer-simulated images and in vivo intracellular recordings to identify and characterize individual neurons implicated in the control of escape. The results of both approaches highlight the influence of behavioural and environmental context in structuring escape. In order to understand how context and the complex flow of signals are processed and translated into behaviour in natural environments it is imperative that future studies take electrophysiology outdoors.